Lipofectamine Mediated Gene Delivery: Cationic Lipid Helps to Overcome the Cell-Surface Barriers in Hepatocytes - Patra, Biswanath (International Journal of Bio-resource and Stress Management, 2011)
The objective of this study is to find effective siRNA delivery vehicle targeting liver, specifically into hepatocytes. Recently developed cationic lipid lipofectamine provide a very high density of positive charges along its backbone and have been reported to be effective in siRNA delivery to target liver cells. We compared lipofectamine mediated siRNA delivery with a cationic polymer based approach (jetPEI), in cultured fresh rat hepatocytes and human embryonic kidney cell line HEK293. We tested plasmids encoding either GFP or luciferase, and a TEX615 red dye labeled oligo to examine efficient translocation into primary hepatocytes in culture. Our results clearly demonstrated the higher efficacy of lipofectamine over jetPEI in targeting hepatocytes for both plasmid and labeled oligo delivery.